Hydrodynamic effects during waste cooking oil transesterification using CFD - Adeyemi, Nabeel A.; Mohiuddin, A. K. M.; Jameel, Ahmed Tariq (2010)
This work is presented as part of a preliminary study to model transesterification of Waste Cooking Oil (WCO). A Computational Fluid dynamics (CFD) technique was used to simulate flow of WCO in a 2 Litre reactor. A turbulent model of the Naviers Stokes' equation was used to solve the transient form of the equation for an axisymmetrical 2-D model and the effect of different impeller bottom distance and baffle were analyzed. Peak mean turbulence energy and dissipative energy rate were recorded at impeller bottom clearance C=0.23T for both baffled and unbaffled system. This provides a basis for a proposed dynamic modelling of transesterification WCO.